The causes of the American Revolution (D. C. Health, 1973)
This book traces the events that led to the American Revolution. It explains the ideas about the right to self-government that began to circulate in the colonies during the 1760s. It discusses the rising tensions as Britain imposed repressive policies on the colonies, which in turn led some American leaders to promote outright independence. Although the war might have been avoided if both sides had been willing to compromise, by 1775 conflict was inevitable.